Fate of nutrients and heavy metals during two-stage digestion and aerobic post-treatment of municipal organic waste. (March 2018) - Knoop, Christine; Tietze, Michael; Dornack, Christina; Raab, Thomas
Highlights: 40% of nutrients in MOW are mineralized during anaerobic and aerobic post-treatment. Higher nutrient release was observed during the anaerobic treatment step. Release of nutrients during treatment is element-specific. Heavy metal loads are not significantly influenced during MOW treatment. A sufficient feedstock quality shall be the first priority of MOW management. Abstract: The biogas technology is a promising approach for the recovery of energy and fertilizer from municipal organic waste (MOW). However, only scarce information on the development of initial nutrient and heavy metal loads during processing is available. Therefore, this study investigates properties of source-separated MOW during treatment in a semi-industrial scale two-stage biogas plant and subsequent digestate composting including impurities removal. Data from 15 batch experiments was investigated by material and substance flow analysis. Results of this study have shown that about 40% of nutrients contained in the MOW inflow are mineralized during anaerobic and subsequent aerobic treatment. A higher nutrient release was observed during the anaerobic treatment step. Additionally, impurities removal causes a significant reduction of final nutrient content. Heavy metal analysis confirmed a high heterogeneity of contamination levels. However, digestion and composting do not seem to significantly impact on total heavy metal loads in the substrate flow.